Performance-based seismic analysis of a reinforced concrete framed tall building - Tripathi, Sujan; Pal, Raju; Aryal, Raman; Sapkota, Sagar Prasad; Luitel, Shree Krishna; Lama, Simaran; Lamichhane, Subash (Journal of Innovations in Engineering Education, 2026)
The seismic hazard in Nepal, highlighted by the 2015 Gorkha earthquake, necessitates the transition from conventional force-based design to more reliable methods for tall buildings. This research presents a performance-based seismic design of a typical 15-story reinforced concrete (RC) framed building with two basements, located in the Kathmandu Valley. The building, designed with a dual system of RC shear walls as per the Nepal National Building Code (NBC 105:2020), was modeled and analyzed using the finite element software ETABS v21.0.0. Nonlinear static (pushover) analysis was used to evaluate the building’s post-yield behavior and to check if it meets the Life Safety performance level. Results showed that at a roof displacement of 0.414 m, the structure performs well above the Life Safety limit (0.336 m) and remains far below the Collapse Prevention level (0.676 m), confirming that no collapse will occur under design-level earthquakes. Plastic hinge formation indicated a ductile failure pattern, with most of the 69 hinges forming in beams, supporting the strong column, weak-beam concept. The study concludes that Performance-Based Design (PBD) offers essential insights regarding a building’s resilience and is recommended for new tall structures in earthquake-prone areas like Nepal.